2007
DOI: 10.1177/0961203307084712
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolate mofetil as induction and maintenance therapy for lupus nephritis: rationale and protocol for the randomized, controlled Aspreva Lupus Management Study (ALMS)

Abstract: The Phase III Aspreva Lupus Management Study (ALMS) will investigate mycophenolate mofetil (MMF) therapy for lupus nephritis (LN). Eligibility criteria include: 12-75 years of age; diagnosis of systemic lupus erythematosus according to revised American College of Rheumatology criteria; and biopsy-demonstrated LN (Class III-V). Randomized patients will receive open-label induction therapy with MMF or cyclophosphamide in combination with corticosteroids for 24 weeks. The primary efficacy endpoint is treatment re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(72 citation statements)
references
References 48 publications
1
67
0
4
Order By: Relevance
“…NCT00377637) has been published. 32 The study was conducted in accordance with the Declaration of Helsinki and the principles of Good Clinical Practice. The institutional review boards at all participating centers approved the protocol, and all patients provided written informed consent.…”
Section: Design Overviewmentioning
confidence: 99%
“…NCT00377637) has been published. 32 The study was conducted in accordance with the Declaration of Helsinki and the principles of Good Clinical Practice. The institutional review boards at all participating centers approved the protocol, and all patients provided written informed consent.…”
Section: Design Overviewmentioning
confidence: 99%
“…Results of the induction study and detailed descriptions of methods for both phases have been reported previously. 13,18 The study was conducted in accordance with the Declaration of Helsinki and Good Clinical Practice principles. The institutional review boards at the participating centers approved the protocol, and all patients or their representatives provided written informed consent.…”
Section: Study Design and Oversightmentioning
confidence: 99%
“…ALMS is an international trial of 370 patients with class III-V lupus nephritis comparing pulse monthly intravenous (IV) cyclophosphamide (CYC) to mycophenolate mofetil (MMF) for the induction of renal response (2,3). The data from this trial provided a rare opportunity to analyze a large population of prospectively followed, well-characterized, ethnically diverse lupus nephritis patients who were treated with two commonly used immunosuppressive agents.…”
Section: Introductionmentioning
confidence: 99%